2013
DOI: 10.1111/jvh.12117
|View full text |Cite
|
Sign up to set email alerts
|

Risk of transmission associated with sharing drug injecting paraphernalia: analysis of recent hepatitis C virus (HCV) infection using cross‐sectional survey data

Abstract: Sharing injecting paraphernalia (containers, filters and water) poses a risk of transmitting the hepatitis C virus (HCV). The prevalence of, and risk of HCV from, such behaviour has not been extensively reported in Europe. People who inject drugs (PWID) were recruited in cross-sectional surveys from services providing sterile injecting equipment across Scotland between 2008 and 2010. Participants completed a questionnaire and provided a blood spot for anonymous testing. Logistic regression was used to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 36 publications
(58 reference statements)
2
73
0
4
Order By: Relevance
“…33 One study looked at the impact of distributing injecting paraphernalia (defined as spoons and filters) by itself, with needles/syringes and in combination with OST. 47 …”
Section: Type Of Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…33 One study looked at the impact of distributing injecting paraphernalia (defined as spoons and filters) by itself, with needles/syringes and in combination with OST. 47 …”
Section: Type Of Interventionsmentioning
confidence: 99%
“…[33][34][35][36][37]59,60 Seventeen studies reported the impact of NSPs, 14,20,[41][42][43][44]47,48,50,54,56,58 including five unpublished sources, [33][34][35]59,60 and four reported combined measures of NSPs with OST, 14,33,44,47 including one unpublished data source. 33 One study looked at the impact of distributing injecting paraphernalia (defined as spoons and filters) by itself, with needles/syringes and in combination with OST.…”
Section: Type Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations